Analysis of The Use of Analogy of Chemical Education Students on The Concept of Chemical Bond - Naqsyahbandi, Fajar; Mulyatun, Mulyatun; Drastisianti, Apriliana; Muhariyansah, Jajang (J-PEK (Jurnal Pembelajaran Kimia), 2022)
The analogy is a valuable pedagogical tool for educators because, by using an analogy, abstract concepts in chemistry can be explained effectively. Therefore, prospective educators need to understand analogies. This qualitative descriptive study aims to analyze and describe the analogy used by chemistry education students on the concept of chemical bonds. The test instrument used the form of 10 open-ended questions been validated by anexpert. The results showed three types of analogies: simple analogies, enriched analogies, and extended analogies. This analogy is still single, with the lowest average percentage in the extended analogy type of 5%, while the enriched analogy type is at a percentage of 24%. The analogy type mostly used by students is a simple analogy type with an average percentage of 31 % , and as much as 40% of students do not analogize the existing concept of chemical bonds.